Pengembangan Sistem Deteksi Gerakan Kepala Sebagai Kontrol Pergerakan Kursi Roda Berbasis Embedded System - Virza Audy Ervanda; Dahnial Syauqy; Fitri Utaminingrum (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Wheelchair was initially very helpful for users with leg defects, But there are problems for users who have more flaws to move their hands so some users are still difficult to use the wheelchair. Based on these problems, Researchers used head movement as an embedded system-based controller as wheelchair control. System will use an MPU6050 sensor which will be placed on the user's forehead and 2 pieces of NodeMCU where 1 NodeMCU on the controller is used as client and 1 NodeMCU in the wheelchair as server. Based on the implementation, by using the complementary the problem of reading angle values caused by noise can be solved so that the output becomes more stable and accurate. From the tests that have been done on 5 subjects, it is known that the initial determination of sensor readings is not 0° but has a range of X-axis angle values ​​of -11.61° to -20.70° with an average of -14.86°. Based on the head movement performed on the test, the average value on the X-axis is 30.24° when it is downward and -40.46 ° when upward. As for the Y-axis obtained and average value of -27.97° when tilt to the left and 26.83° when tilt to right. For data transmission, the system has 100% success rate with average response time about 52 ms.